2022
DOI: 10.1186/s12978-021-01313-6
|View full text |Cite
|
Sign up to set email alerts
|

Fertility trends and comparisons in a historical cohort of US women with primary infertility

Abstract: Background There is growing interest in long-term outcomes following infertility and infertility treatment. However, there are few detailed longitudinal cohorts available for this work. This study aimed to assemble a historical cohort of women with primary infertility and age-matched controls to evaluate fertility trends, sequelae, and sociodemographic differences. Described here are cohort group characteristics and associated reproductive trends over time. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Our previous study highlighted that characteristics of our cohort of women with primary infertility are consistent with other studies of women with primary infertility, supporting its use as a representative sample for future study. 9 Although the length of follow-up and number of women included in our cohort contribute to the strength and effect of our findings, our study is not without limitations. In our analysis stratified by the primary infertility indication, particularly for those with endometriosis as the indication, some models may be considered overfit using the rule of thumb of 10-15 events per each covariate included in the regression model.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our previous study highlighted that characteristics of our cohort of women with primary infertility are consistent with other studies of women with primary infertility, supporting its use as a representative sample for future study. 9 Although the length of follow-up and number of women included in our cohort contribute to the strength and effect of our findings, our study is not without limitations. In our analysis stratified by the primary infertility indication, particularly for those with endometriosis as the indication, some models may be considered overfit using the rule of thumb of 10-15 events per each covariate included in the regression model.…”
Section: Discussionmentioning
confidence: 85%
“…12 This study was deemed IRB-exempt because it included secondary use of information (chart review). A detailed description of the cohort used in this study has been published previously 9 and is summarized here. A total of 3,489 women aged 18-50 years with at least one diagnosis code for infertility were identified in the REP. By manual chart review, a cohort of 1,001 women had a confirmed diagnosis of primary infertility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of IgA present in the sperm and pre-ejaculate has yet to be confirmed. However, it appears that both local syntheses, primarily in the penile urethra and circulation, contribute to the Ig pool in these fluids, based on the molecular characteristics (Chantler, Sharma and Sharman, 1989;Sadecki, et al, 2022). The sperm parameters such as total progressive sperm motility/ejaculate and round cells count were significantly correlated with DFI that was agreed by a previous study, whereas the other sperm parameters such as normal sperm morphology and the sperm count did not correlate with DFI.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for primary infertility were ovulatory dysfunction and unexplained infertility, whereas clomiphene has been prescribed most widely among fertility drug ( Sadecki et al, 2022 ). ART development and administration can considerably raise the clinical pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%